The prevalence of metabolic syndrome according to various definitions and hypertriglyceridemic-waist in Malaysian adults - Mohd Zainuddin, Laila Ruwaida; Isa, Nur Firdaus; Wan Muda, Wan Manan; Jan Mohamed, Hamid Jan (Isfahan University of Medical Sciences(IUMS), 2011)
Objectives: Metabolic syndrome can be diagnosed according to several different criteria such as the latest International Diabetes Federation (IDF), National Cholesterol Education Program Adult Treatment Program III (NCEP ATPIII), and World Health Organization (WHO). The objectives of this study were to determine the prevalence of metabolic syndrome and the concordance between the above mentioned definition, and hypertriglyceridemicwaist criteria. Methods: This cross sectional study was done in Bachok, Malaysia and involved 298 respondents aged between 18 to 70 years. Multistage random sampling method was used to identify study locations while convenient random sampling method was applied to select individuals. Hypertriglyceridemic waist was defined from an internationally acceptable cut-off criterion. Kappa statistic (κ test) was used to determine the concordance between various definitions and hypertriglyceridemic-waist. Results: The prevalence of metabolic syndrome based on different definitions was 32.2% (IDF), 28.5% (NCEP ATP III) and 12.4% (modified WHO). The prevalence of hypertriglyceridemic-waist was 19.7% and based on the IDF criteria a total of 97.5% participants with hypertriglyceridemic-waist had metabolic syndrome. The IDF criteria showed the highest concordance with NCEP ATPIII criteria (κ = 0.63), followed by hypertriglyceridemic-waist criteria (κ = 0.62) and WHO criteria (κ = 0.26). Conclusions: The prevalence of metabolic syndrome was highest using the IDF criteria compared to NCEP ATPIII, modified WHO and hypertriglyceridemic-waist. There was a good concordance of IDF criteria with NCEP ATP III and hypertriglyceridemic-waist criteria.